2016
DOI: 10.1021/acscatal.6b01850
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium-Catalyzed Intermolecular Double Hydrophosphination of Alkynes with a Primary Phosphine

Abstract: Catalytic double hydrophosphination of internal alkynes and primary phosphines is possible using a zirconium complex, [κ5 -N,N,N,N,C-(Me3SiNCH2CH2)2NCH2CH2NSiMe2CH]Zr (1). The reaction proceeds via stepwise hydrophosphination to give vinyl phosphine products, which can be isolated or further converted to the respective 1,2-bis­(phosphino)­ethane (i.e., double hydrophosphination). The catalysis is highly selective for formation of secondary phosphine products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 35 publications
(74 reference statements)
3
37
0
Order By: Relevance
“…With the success of trapping reactions with 2,3‐dimethyl‐1,3‐butadiene, more challenging substrates were attempted. Treatment of PhPH 2 with five equivalents of diphenylacetylene and 5 mol % of 1 gave double hydrophosphination of the alkyne in 42 % conversion with trace amounts of 1,2,3,4,5‐pentaphenylphosphole, as was measured by 31 P NMR spectroscopy . Formation of phosphole in greater than 10 % was achieved by running the same reaction under 1 atm of hydrogen.…”
Section: Methodsmentioning
confidence: 76%
“…With the success of trapping reactions with 2,3‐dimethyl‐1,3‐butadiene, more challenging substrates were attempted. Treatment of PhPH 2 with five equivalents of diphenylacetylene and 5 mol % of 1 gave double hydrophosphination of the alkyne in 42 % conversion with trace amounts of 1,2,3,4,5‐pentaphenylphosphole, as was measured by 31 P NMR spectroscopy . Formation of phosphole in greater than 10 % was achieved by running the same reaction under 1 atm of hydrogen.…”
Section: Methodsmentioning
confidence: 76%
“…These reactions under extended periods provided exclusively the single P–H bond activation product, and none of the double hydrophosphination product was observed. In prior studies with 1 , double hydrophosphination has been observed for a primary phosphine substrate . These observations and prior reactivity of 1 suggest that the second hydrophosphination reaction is disfavored due to steric constraints and these reactions were not pursued further.…”
Section: Resultsmentioning
confidence: 99%
“…Theh ydrophosphination of olefins and alkynes has received much attention in the last decade, [4] but the use of heterocumulene substrates has been less explored, with examples of precatalysts for these reactions being limited to rare-earth, [5] alkali-metal, [6] and group 2c omplexes. [7] The hydrophosphination of organic isocyanates,yielding phosphinocarboxamide products,islimited to afew recent examples, all of which are catalyzed by f-block complexes.…”
Section: Organophosphoruscompoundsareavitalclassofchemicalsmentioning
confidence: 99%